Improvement in Liver Transplant Outcomes From Older Donors: A US National Analysis. Issue 2 (August 2019) - Gao, Qimeng; Mulvihill, Michael S.; Scheuermann, Uwe; Davis, Robert P.; Yerxa, John; Yerokun, Babatunde A.; Hartwig, Matthew G.; Sudan, Debra L.; Knechtle, Stuart J.; Barbas, Andrew S.
Abstract : Objective: To investigate trends in long-term graft and patient outcomes following liver transplantation using grafts from donors ≥60 years old. Summary Background Data: The scarcity of donor livers has led to increased utilization of organs from donors ≥60 years old. However, few studies have examined how long-term transplant outcomes from older donors have evolved over time. Methods: The OPTN/UNOS database was queried for all first-time isolated adult liver transplants. We identified 14, 796 adult liver transplant using donors ≧60-year-old suitable for analysis from 1990 to 2014. Cohorts were then developed based on 5-year intervals of transplant date. Kaplan–Meier analysis was used to compare graft and patient survival for recipients from older donor across each 5-year era. Results: Utilization of donor grafts ≥60 years old increased steadily for the first 15 years of the study, but has leveled off over the last 10 years. Comparison of the earliest and latest eras in the study was notable for an increase in median recipient age (51 vs. 59, P < 0.001) and reduction in median cold ischemic time (10 vs. 6 h, P = 0.001). Unadjusted 5-year graft and patient survival has improved significantly over time ( P < 0.0001). More importantly, the discrepancy in survival between older and younger grafts has narrowed substantially over time ( P < 0.0001). Conclusions: This study demonstrates significant improvement in transplant outcomes with donor grafts ≥60-years old and supports increased but judicious use of extended criteria donors liver grafts. Improved patient selection and reduction in cold ischemia time appear to be contributing factors.